Empirical Models for Power and Energy Requirements II : A Powered Implement Operation in Serdang Sandy Clay Loam, Malaysia - A. F. Kheiralla; A. Yahya; M. Zohadie; W. Ishak (Universitas Gadjah Mada, 2003)
Power and energy requirements were measured with an instrumented tractor for rotary tilling in Serdang sandy clay loam soil. The effects of travel speed and rotor speed upon the measured data were investigated. Power model from orthogonal regression analysis was formulated based on linear and quadratic functions of travel speed and bite length. Fuel consumption model from regression analysis was formulated based on linear tractor PTO power as well as linear equivalent tractor PTO power. Fuel consumption rates predicted by ASAE D497.3 were found to be 25% to 28% overestimates of the values predicted by the model developed. However, fuel consumption rates reported by OECD Tractor Test were found to be 1% to 9% lower than the fuel consumption rates predicted by the model developed. A comparison of power and energy requirements for both powered and draught implements showed that the disk harrow was the most energy efficient implement in terms of fuel consumption and specific energy followed by the rotary tiller, disk plough and mouldboard. Finally, average PTO power, fuel consumption, wheel slip, wheel power and specific energy for a powered implement are presented.